Issues for the future of Vocational Education and Training : editorial - Esser, Friedrich Hubert [Verfasser] (My University, 2017)
"In looking at issues for the future of VET, we are consci-ous of the fact that many topics relating to the further development of the dual system have a long tradition. The four topics that I will examine in greater detail below – digitalisation, matching problems on the training market, integration of refugees and internationalisation - do not, therefore, pose any questions that are entirely new. Nevertheless, it is necessary to localise these issues in the present and the future. This means clarifying their current relevance for the profiling of vocational education and training and the associated process of illustrating prospective action options." (author's abstract ; BIBB-Doku)
Zukunftsfragen zur Berufsbildung
Keywords: P 1.5 Migranten; Berufsbildung; Digitalisierung; Mismatch; Flüchtling; Internationalisierung